Process integration study of a biorefinery producing ethylene from lignocellulosic feedstock for a chemical cluster - Arvidsson, Maria; Lundin, Björn (My University, 2011)
A chemical cluster producing a variety of products is situated in Stenungsund, Sweden. In 2010 the ethylene consumption of the cluster (currently covered by import and a steam cracker converting e.g. naphta) increased due to the start-up of a new polyethylene (PE) plant by Borealis AB. This work investigates the opportunity to cover the current ethylene import (i.e. 200 000 tonnes/year) by the introduction of a biorefinery plant (reducing fossil fuel dependence and greenhouse gas (GHG) emissions from the cluster). High material and energy efficiency is of utmost importance to achieve economic competitiveness. Hence, heat integration is essential. A simulation model for a biorefinery is established in Aspen Plus based on literature review and personal contacts with experts. A process integration study is conducted using pinch analysis of simulation results. The aim is to investigate the integration consequences (e.g. potential energy savings and economical aspects) of combining a stand-alone lignocellulosic ethanol and a stand-alone ethanol dehydration plant into a biorefinery producing ethylene from lignocellulosic feedstock via the fermentation route. Several process configurations of the biorefinery are investigated, e.g. the integration of the biorefinery with the existing cluster based on results obtained from a total site analysis (TSA) (Hackl, et al., 2010). In the lignocellulosic ethanol production spruce (749 MW) is converted to ethanol (337 MW) and a lignin-rich co-product (370 MW), which can be utilised as fuel in a combined heat and power (CHP) plant supplying steam (for hot utility and direct injection into process streams) and electricity. The stand-alone ethanol plant results in excess solid residues (86 MW) and electricity (24 MWel). In the ethylene production, ethanol (337 MW) is converted to ethylene (307 MW). The stand-alone ethylene plant requires external fuel (16 MW) to cover hot utility demand. Moreover, electricity (4 MWel) and steam for direct injection (25 MW) must be produced externally. The results indicate that energy savings (40% and 28% reduction of minimum hot and cold utility respectively) can be achieved by integrating the two stand-alone processes into a biorefinery. Moreover, the integration opportunity to eliminate external fuel, steam and electricity requirements by firing of excess solid residues arises. It is shown that the minimum hot utility demand can be further reduced by 59% by introducing a MVR in the biorefinery (Bio-MVR), which corresponds to a 75% reduction compared with the two stand-alone processes. The results show that the excess solid residues of the biorefinery can eliminate the external fuel requirement by flue gas integration or deliver VHP (41 bar) steam to the existing cluster. The lowest ethylene production cost (1.0 €/kg ethylene) is obtained for the Bio-MVR.
Keywords: Energi; Hållbar utveckling; Kemiska processer; Energy; Sustainable Development; Chemical Process Engineering